Efeitos do atraso em tarefas de discriminação condicional em participantes com e sem deficiência intelectual - Teixeira, Isabela de Oliveira (Universidade Federal de São Carlos, 2019)
Stimulus discrimination is an important repertoire, which is the basis for acquiring complex skills. Investigating critical variables related to the discrimination process is particularly important for participants with some type of intellectual disability and/or developmental delay. The present study had the objectives of analyzing the effect of different delay times on tasks of conditional, identity, and arbitrary discrimination in adolescents with and without intellectual disability, and of identifying, through participants’ reports, precurrent behaviors during the time between the removal of the sample stimuli and presentation of the comparison stimuli. Participants were eight individuals with no disability and six with intellectual disabilities. They were aged between eleven and fourteen years old and attended regular schools. Five participants were boys with typical development and two were boys with intellectual disability (one had Down syndrome). There were three girls with typical development and four with intellectual disability (one had Down syndrome). The procedure consisted of pre-training; teaching identity relations through matching-to-sample (MTS), with continuous and intermittent reinforcement; delayed matching-to-sample (DMTS) tests, with 0, 2, 4, 6, and 8-second delays; teaching arbitrary relationships through MTS, with continuous and intermittent reinforcement and testing with DMTS, with 0, 2, 4, 6, and 8-second delays. After the last experimental session, participants were asked about any strategies used during the DMTS tasks. We analyzed data individually by comparing each participant’s performance throughout the procedure (training and tests) for identity and arbitrary relations. The results showed that the eight participants without disabilities and two participants with intellectual disabilities went through the identity and arbitrary conditional discrimination training and tests using the proposed procedure. Four participants with intellectual disability went through the proposed identity training but required an additional procedure to establish arbitrary relations. As the delay increased, performance decreased, especially for participants with intellectual disabilities – specifically those with Down syndrome. Performance was more impaired in the arbitrary than in the identity conditional discrimination tasks. According to participants’ reports, the most obvious strategy used during the procedure was “vocal repetition”. However, participants with disabilities had difficulties in reporting the strategy used, unlike the participants without intellectual disabilities, who did not. These results are relevant to further our understanding of ‘delay’ as a variable controlling recall behavior (“remembering”) and may improve teaching procedures, especially for precurrent behaviors of people with intellectual disabilities
Effects of delay in discrimination conditional tasks on participants with and without intellectual disability
Keywords: Educação Especial; Deficiência intelectual; Memória; Special Education; Intellectual Disability; Memory; Delayed Matching to Sample (DMTS); CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM